Livro didático de estudos sociais: um tipo de artefato de produção cultural marcado por continuidades e resistências aos ideais da Ditadura Militar (1970-1980) - Resende Filho, Carlos Moura de (2014)
The present study aimed to analyze two textbooks for Social Studies 1st grade published in the period 1970-1980, observing possible resistance to the ideals of the Military Dictatorship, using laws, ordinances and regulations of the time as a secondary source research to further analyze Textbook of Social Studies, performing the intersection of sources; similarly examined whether what form of control and persuasion that the military government had about the same, when we analyzed the curriculum proposals for the period. Studies textbooks in Brazil have grown considerably, and has shown the importance of teaching resource as a source of research for the History of Education. In this paper, we discuss the textbooks for Social Studies, based on the categories of analysis de Certeau (2012) Strategies and Tactics and Oliveira (1981) "Critical Germ" in order to work through them the concept of resistance. Therefore, we believe that such research became relevant, as the historical production, which has as its source the textbook during the Military Dictatorship has often seen the spread of the dominant ideology in this teaching resource. Examples of such research can be seen in Brazil (MOLINA, 1987; FREITAG, 1993, DO 1991) and Paraíba (ALBUQUERQUE, 2006). Thus we agree with Munakata (2003) that identifies this period research devoted to textbooks, in order to "catch" the same, the presence of the ideology of the time. However, it is still incipient scientific production that examines how the authors of textbooks for Social Studies showed any resistance to the ideal broadcast by the Military Dictatorship. Thus, we employed the perspective of the New Cultural History (NHC), as it seeks to see history through a new perspective, distinct from linear and traditional. In this sense, Burke emphasizes that the NHC has enabled the expansion of the fields of research, as well as sources. Thus, the present study examined textbooks for Social Studies, in which were perceptible images and text fragments that allowed us to demonstrate that the authors of these books used resources and means to circumvent the military ideal, albeit incipient form.